Demographic Structure and Municipal Financial Performance in Boyacá, Colombia (2019)
In this paper we analyze the correlation between the demographic structure of the municipalities of the state of Boyacá (Colombia) and their financial development for 2015. The aim is to determine theoretically and empirically if there is a correspondence between the reduced population observed in the municipal entities of Boyacá and the financial performance of the municipalities, by means of a quantitative study of linear correlation among the two variables cited, from institutional data, supporting the results with the relevant theoretical postulates. We conclude that there is a strong relationship concerning the population size and the fiscal development of the entities of the department, where the first variable generates a negative trend in municipal financial indicators, which implies immense institutional challenges for the entities.